Cortical endogenic neural regeneration of adult rat after traumatic brain injury. - Xin Yi; Guohua Jin; Xinhua Zhang; Weifeng Mao; Haoming Li; Jianbing Qin; Jinhong Shi; Kui Dai; Fan Zhang (PLoS ONE, 2013)
Focal and diffuse neuronal loss happened after traumatic brain injury (TBI). With little in the way of effective repair, recent interest has focused on endogenic neural progenitor cells (NPCs) as a potential method for regeneration. Whether endogenic neural regeneration happened in the cortex of adult rat after TBI remains to be determined. In this study, rats were divided into a sham group and a TBI group, and the rat model of medium TBI was induced by controlled cortical impact. Rats were injected with BrdU at 1 to 7 days post-injury (dpi) to allow identification of differentiated cells and sacrificed at 1, 3, 7, 14 and 28 dpi for immunofluorescence. Results showed nestin(+)/sox-2(+) NPCs and GFAP(+)/sox-2(+) radial glial (RG)-like cells emerged in peri-injured cortex at 1, 3, 7, 14 dpi and peaked at 3 dpi. The number of GFAP(+)/sox-2(+) cells was less than that of nestin(+)/sox-2(+) cells. Nestin(+)/sox-2(+) cells from posterior periventricle (pPV) immigrated into peri-injured cortex through corpus callosum (CC) were found. DCX(+)/BrdU(+) newborn immature neurons in peri-injured cortex were found only at 3, 7, 14 dpi. A few MAP-2(+)/BrdU(+) newborn neurons in peri-injured cortex were found only at 7 and 14 dpi. NeuN(+)/BrdU(+) mature neurons were not found in peri-injured cortex at 1, 3, 7, 14 and 28 dpi. While GFAP(+)/BrdU(+) astrocytes emerged in peri-injured cortex at 1, 3, 7, 14, 28 dpi and peaked at 7 dpi then kept in a stable state. In the corresponding time point, the percentage of GFAP(+)/BrdU(+) astrocytes in BrdU(+) cells was more than that of NPCs or newborn neurons. No CNP(+)/BrdU(+) oligodendrocytes were found in peri-injured cortex. These findings suggest that NPCs from pPV and reactive RG-like cells emerge in peri-injured cortex of adult rats after TBI. It can differentiate into immature neurons and astrocytes, but the former fail to grow up to mature neurons.